Low-dose interleukin-2 in patients with stable ischaemic heart disease and acute coronary syndromes (LILACS): protocol and study rationale for a randomised, double-blind, placebo-controlled, phase I/II clinical trial. Issue 9 (17th September 2018) - Zhao, Tian Xiao; Kostapanos, Michalis; Griffiths, Charmaine; Arbon, Emma L; Hubsch, Annette; Kaloyirou, Fotini; Helmy, Joanna; Hoole, Stephen P; Rudd, James H F; Wood, Graham; Burling, Keith; Bond, Simon; et al.
Abstract : Introduction: Inflammation and dysregulated immune responses play a crucial role in atherosclerosis, underlying ischaemic heart disease (IHD) and acute coronary syndromes (ACSs). Immune responses are also major determinants of the postischaemic injury in myocardial infarction. Regulatory T cells (CD4 + CD25 + FOXP3 + ; Treg) induce immune tolerance and preserve immune homeostasis. Recent in vivo studies suggested that low-dose interleukin-2 (IL-2) can increase Treg cell numbers. Aldesleukin is a human recombinant form of IL-2 that has been used therapeutically in several autoimmune diseases. However, its safety and efficacy is unknown in the setting of coronary artery disease. Method and analysis: Low-dose interleukin-2 in patients with stable ischaemic heart disease and acute coronary syndromes is a single-centre, first-in-class, dose-escalation, two-part clinical trial. Patients with stable IHD (part A) and ACS (part B) will be randomised to receive either IL-2 (aldesleukin; dose range 0.3–3×10 6 IU) or placebo once daily, given subcutaneously, for five consecutive days. Part A will have five dose levels with five patients in each group. Group 1 will receive a dose of 0.3×10 6 IU, while the dose for the remaining four groups will be determined on completion of the preceding group. Part B will have four dose levels with eight patients in each group. The dose of the first group will be based on part A. Doses for each of the subsequent three groups will similarly be determined after completion of the previous group. The primary endpoint is safety and tolerability of aldesleukin and to determine the dose that increases mean circulating Treg levels by at least 75%. Ethics and dissemination: The study received a favourable opinion by the Greater Manchester Central Research Ethics Committee, UK (17/NW/0012). The results of this study will be reported through peer-reviewed journals, conference presentations and an internal organisational report. Trial registration number: NCT03113773; Pre-results .